Reference-Dependent Preferences A Theoretical and Experimental Investigation of Individual Reference-Point Formation - Stommel, Evelyn. (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2013)
Most of our daily decisions are made under uncertainty and risk, without complete information about all relevant aspects. We all constantly make such decisions, from the simplest <U+001c>should I take my raincoat today? to more serious examples, such as those on investment and portfolio decisions, holding of shares, insurance patterns, or negotiation processes. Within these situations, the bounded rationality of individuals and institutions towards risk and uncertainty is embedded. The central theory underlying this study is prospect theory, an adequate model to predict the real and most often bounded rationality of human behavior given certain incentives, preferences, and constraints. Evelyn Stommel investigates a crucial question within behavioral economics, namely the research on reference points within human decision making processes. Based on experimental investigations, she focuses three key challenges: what constitutes a reference point, the process of the formation of a reference point, and factors influencing the formation of reference points. Contents ʺ Literature Review and Research Gaps ʺ Reference-Dependent Preferences ʺ Reference Point Adaptation and Formation ʺ Risk and Uncertainty ʺ Personality Traits and Affects Target Groups ʺ Researchers and students in the field of Business Administration with focus on behavioral economics or organizational theory. ʺ Practitioners such as managers and consultants interested in decision making processes under risk and uncertainty. About the Author Evelyn Stommel has been a doctoral student at Germany<U+0018>s Wissenschaftliche Hochschule f<U+00fc>r Unternehmensf<U+00fc>hrung (WHU) <U+0013> Otto Beisheim School of Management. Today, she works as an Inhouse Consultant for a German DAX 30 industrial company.